2013
DOI: 10.1073/pnas.1310300110
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate heat dissipation ignites brown fat thermogenesis in mice with a mutant thyroid hormone receptor α1

Abstract: Thyroid hormone is a major regulator of thermogenesis, acting both in peripheral organs and on central autonomic pathways. Mice heterozygous for a point mutation in thyroid hormone receptor α1 display increased thermogenesis as a consequence of high sympathetic brown fat stimulation. Surprisingly, despite the hypermetabolism, their body temperature is not elevated. Here we show, using isolated tail arteries, that defective thyroid hormone receptor α1 signaling impairs acetylcholine-mediated vascular relaxation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
89
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(100 citation statements)
references
References 43 publications
(53 reference statements)
10
89
1
Order By: Relevance
“…However, our data do not completely exclude a possible defect in the cardiovascular systems of HF-fed Pemt Ϫ / Ϫ mice and a potential connection with cold-induced hypothermia in these mice. On one hand, increased heat loss due to defective peripheral vessel constriction has been linked to cold-sensitivity in thyroid hormone receptor ␣ 1 mutant mice ( 31 ). On the other hand, HF-fed Pemt Ϫ / Ϫ mice have choline defi ciency (unpublished observations), which might reduce acetylcholine ( 32 ), a well-known vascular dilator ( 33 ).…”
Section: Systolic Hypertension and Reduced Cardiac Output In Hf-fed Pmentioning
confidence: 99%
“…However, our data do not completely exclude a possible defect in the cardiovascular systems of HF-fed Pemt Ϫ / Ϫ mice and a potential connection with cold-induced hypothermia in these mice. On one hand, increased heat loss due to defective peripheral vessel constriction has been linked to cold-sensitivity in thyroid hormone receptor ␣ 1 mutant mice ( 31 ). On the other hand, HF-fed Pemt Ϫ / Ϫ mice have choline defi ciency (unpublished observations), which might reduce acetylcholine ( 32 ), a well-known vascular dilator ( 33 ).…”
Section: Systolic Hypertension and Reduced Cardiac Output In Hf-fed Pmentioning
confidence: 99%
“…79 These mice had a significantly higher maximum interscapular skin temperature at thermoneutral room temperature (with increased whole body weight-adjusted oxygen consumption) when compared to wild type mice. 80 The body temperature of p62 knockout mice (as measured with a thermal camera), as well as energy expenditure, following cold exposure was lower than that of wild type mice. 81 In this same study, p62 knockout mice gained more weight than wild type mice when both groups were fed normal chow diet and high fat diet.…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 94%
“…Lee and colleagues demonstrated that T 3 induced UCP1 expression in human multipotent adiposederived stem cells [14]. This takes place through thyroid receptor (TR ) gene expression and regulates thermogenesis in BAT by TR isoform [26,27]. It is well known that T1AM is not a ligand for TRs.…”
Section: DI Is Sc Cu Us Ss Si Io On Nmentioning
confidence: 99%